2017
DOI: 10.1177/0885328217745699
|View full text |Cite
|
Sign up to set email alerts
|

Role of geometrical cues in bone marrow-derived mesenchymal stem cell survival, growth and osteogenic differentiation

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. AbstractMesenchymal stem cells (MSCs) play a vital role in bone formation process by differentiating into osteoblasts, in a tissue that offers not a flat but a discontinuous threedimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…Moreover, 3D culture in Matrigel strongly mimics the physiological condition in vivo . Many studies have reported that 3D culture provides an optimal environment for cellular adhesion and communication [ 23 , 26 ]. The 3D constructs represent a completely different environment, due to different signaling pathway activity compared to 2D culture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3D culture in Matrigel strongly mimics the physiological condition in vivo . Many studies have reported that 3D culture provides an optimal environment for cellular adhesion and communication [ 23 , 26 ]. The 3D constructs represent a completely different environment, due to different signaling pathway activity compared to 2D culture.…”
Section: Discussionmentioning
confidence: 99%
“…33 Low-adherent 48-well plates were prepared using a coating with 200 ÎŒl of 1% w/v solution of poly(2-hydroxyethyl methacrylate) (poly-HEMA) (Sigma-Aldrich, UK) and 95% ethanol. 36 Cells were cultured in standard medium (low glucose DMEM supplemented with 10% foetal calf serum, 1% penicillin and streptomycin, 1% L-glutamine, 1% of non-essential amino acid) at 37°C and 5% CO 2 for 12 days.…”
Section: Cell Culture Studiesmentioning
confidence: 99%
“…A three-dimensional (3D) culture environment can promote the osteogenic differentiation of adipose tissue-derived stem cells (ADSCs) induced by dexamethasone in vitro [11]. However, traditional two-dimensional (2D) culture involves seeding cells into plastic plates, which greatly reduces their differentiation potential [12]. In the present study, Cellmatrix hydrogel was used to load ADSCs into the 3D culture medium.…”
Section: Discussionmentioning
confidence: 99%